The Effectiveness of Prolactin Hormone Administration on Ovulation in Postpartum Female Mice (Mus musculus) - Merta, I Wayan; Kusmiyati, Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The prolactin hormone produced by the anterior pituitary gland plays an important role in the reproductive system, such as stimulating breast milk production and regulating the menstrual cycle in women, as well as stimulating sperm production and sex drive in men. This study aims to 1) examine the effectiveness of prolactin hormone administration on ovulation in postpartum female mice (Mus musculus). 2) contribute to the study material of animal physiology courses, particularly on endocrine topics. This research employed a true experimental design using a completely randomized design (CRD). The research samples were female Mus musculus mice of the BALB/C strain, approximately 4 months old, weighing between 25–30 grams, healthy, and non-pregnant. The data obtained were analyzed using a one-way analysis of variance (ANOVA) (F-test) with a significance level of 0.05, followed by a Least Significant Difference (LSD) test. The results showed that the significance value (p) = 0.001 < α = 0.05, indicating that the administration of prolactin hormone had a significant effect in reducing ovulation in postpartum female Mus musculus mice.